Microparticles in systemic sclerosis: Potential pro‐inflammatory mediators and pulmonary hypertension biomarkers. Issue 7 (12th February 2019) - Lammi, Matthew R.; Saketkoo, Lesley Ann; Okpechi, Samuel C.; Ghonim, Mohamed A.; Wyczechowska, Dorota; Bauer, Natalie; Pyakurel, Kusma; Saito, Saito; deBoisblanc, Bennett P.; Boulares, A. Hamid
ABSTRACT: Background and objective: Endothelial microparticles (EMP) are submicron vesicles released from endothelial cells. We aimed to determine the utility of EMP as biomarkers of pulmonary arterial hypertension (PAH) in systemic sclerosis (SSc) patients and the pathogenic role of microparticles (MP) in vascular inflammation. Methods: Levels of EMP (CD144+, CD31+, CD62E+ and CD143+) were compared between three groups (10 SSc patients with PAH, 10 SSc patients without pulmonary hypertension (no‐PH) and 10 healthy age‐ and sex‐matched controls). Human pulmonary artery endothelial cells (HPAEC) were exposed in vitro to MP obtained from SSc patients or healthy controls, and levels of cytokines and inflammatory adhesion molecules were compared. Results: CD144+ EMP were significantly higher in the SSc‐PAH group compared to either the SSc‐no PH or healthy controls (diagnostic accuracy 80%, P  = 0.02). Compared to controls, SSc patients had higher CD31+/CD62E+ ratios, indicating larger contributions of apoptosis to EMP release ( P  = 0.04). Patients with limited SSc had significantly higher levels of CD143+ EMP compared to those with diffuse subtype ( P  = 0.008). When HPAEC were exposed to MP from SSc patients, there was a significant increase in inflammatory cytokines and adhesion molecules. Interestingly, exposure to healthy control MP caused a reduction in inflammatory markers. Conclusion: EMP (particularly CD144+) are promising biomarkers of PAH in SSc but require further study. MP isolated from SSc patients induced an increase in endothelial cell inflammation and may be an important pathogenic factor in SSc. Abstract : CD144+ endothelial microparticles (MP) were significantly higher in systemic sclerosis (SSc) patients with pulmonary hypertension (PH) compared to SSc patients without PH, suggesting that they may be a biomarker of SSc‐PH. MP from SSc patients also increased endothelial inflammation in vitro, indicating a possible pathogenic role in this condition.